2008
DOI: 10.1029/2007gc001677
|View full text |Cite
|
Sign up to set email alerts
|

Effect of three‐dimensional slab geometry on deformation in the mantle wedge: Implications for shear wave anisotropy

Abstract: [1] Shear-wave splitting observations from many subduction zones show complex patterns of seismic anisotropy that commonly have trench-parallel fast directions. Three-dimensional flow may give rise to trench-parallel stretching and provide an explanation for these patterns of seismic anisotropy. Along-strike variations in slab geometry produce trench-parallel pressure gradients and are therefore a possible mechanism for three-dimensional flow. In this study we quantify the effects of variable slab dip, curved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
110
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(119 citation statements)
references
References 46 publications
8
110
0
1
Order By: Relevance
“…Interestingly, we see that there is a flow perpendicular to the plate boundary in the area enclosed by white dashed line, and the magnitude of this velocity component is much larger than that of radial velocity component. Similar flow is also reported by Kneller and van Keken (2008) in 3D rectangular geometry. Nakajima et al (2006) examined the fast directions of shear-wave splitting near the plate junction of the southwestern part of the Kurile arc and the northeastern Japan arc.…”
Section: Resultssupporting
confidence: 76%
“…Interestingly, we see that there is a flow perpendicular to the plate boundary in the area enclosed by white dashed line, and the magnitude of this velocity component is much larger than that of radial velocity component. Similar flow is also reported by Kneller and van Keken (2008) in 3D rectangular geometry. Nakajima et al (2006) examined the fast directions of shear-wave splitting near the plate junction of the southwestern part of the Kurile arc and the northeastern Japan arc.…”
Section: Resultssupporting
confidence: 76%
“…Liquidus pressures and temperatures for the most primitive basalts (>6 wt.% MgO only) were calculated with the silica activity geobarometer and olivineliquid geothermometer of Lee et al (2009), using whole-rock data adjusted into equilibrium with Fo 90 mantle through incremental addition of olivine (assuming Fe 3+ / Fe = 0.15) ( Table S1). Since water contents are not known for most GVB basalts, 0% H 2 O was assumed for all samples.…”
Section: Mantle Melting Conditionsmentioning
confidence: 99%
“…However, seismic anisotropy data, 3-D numerical modeling, and experimental studies have shown that mantle flow in subduction zones may be much more complex, especially at and near the terminations of the arcs (Kneller and van Keken, 2008;Long and Silver, 2009;Long and Wirth, 2013;MacDougall et al, 2014;Schellart, 2010Schellart, , 2004. Because the compositions of primary arc magmas reflect the composition of the mantle wedge (variably modified by slabderived components), spatial variations in the geochemistry of arc magmas provide independent evidence for circulation patterns in the mantle wedge.…”
Section: Introductionmentioning
confidence: 96%
“…Karato et al 2001;Royden & Husson 2006;Billen & Hirth 2007;Cížková et al 2007;Schettino & Tassi 2012), with potential implications for slab rollback and mantle flow in the subduction zone. For instance, tearing of the subducted oceanic lithosphere creates a gap in the plate through which 3-D toroidal flow of asthenospheric mantle material may occur (Peyton et al 2001;Kneller & van Keken 2008;Zandt & Humphreys 2008). This process would shortcut (Dougherty et al 2012;Dougherty & Clayton 2014) the trench-parallel flow that occurs beneath the slab as it rolls back, and transfer material into the overlying mantle wedge (Russo & Silver 1994;Schellart 2004;Jadamec & Billen 2010).…”
Section: Introductionmentioning
confidence: 99%